Higher education exit exams and labor market readiness: A systematic review - Teshome, Samson Worku (Indonesian Journal of Educational Management and Leadership, 2025)
Purpose − Exit exams are a critical component of higher education systems worldwide, serving as a benchmark for assessing students' readiness for graduation and professional practice. However, the relationship between exit exams and labor market readiness remains underexplored. This systematic literature review aims to examine the role of exit exams in preparing students for the labor market, focusing on their impact on employability, skill acquisition, and career readiness. Method − Using the PRISMA framework and PICO strategy, the researcher conducted a comprehensive search across multiple databases, identifying relevant studies published between 1994 and 2024. The PRIMA framework followed identification, screening, eligibility and inclusion stages. The PICO framework was used to structure the research questions by breaking them down into four components: Population, Intervention, Comparison, and Outcome. The review synthesizes findings from 31 studies, highlighting the dual role of exit exams as both a motivator for academic achievement and a source of labor market preparedness. Findings − The results indicate that while exit exams can enhance educational outcomes, their impact on labor market readiness is influenced by a variety of factors, including the alignment of exam content with industry needs, the level of support provided to students, and the cultural context in which the exams are administered. The discussion section delves into the implications of these findings for educational policy and practice, suggesting strategies to enhance the labor market readiness of graduates. This review underscores the need for a balanced approach to exit exams that prioritizes both academic rigor and career preparedness.